Effect of Gymnema lactiferum tea brew on type 2 diabetes mellitus: A double-blind, randomised active-controlled phase III clinical trial - Kulanayagam, K.; Sivansuthan, S.; Surenthirakumaran, R.; Thiyahiny, S.N.; Vithegi, K.; Sirimal, P. (Elsevier, 2024)
Background: Gymnema lactiferum is an edible leafy vegetable plant in the family of Apocynaceae. It has been used to control diabetes in the northern part of Sri Lanka for several decades and used as a leaf vegetable from the ancient period. However, this plant was not clinically tested for its claimed antidiabetic properties. Therefore, this study was conducted in Teaching Hospital Jaffna to establish the efficacy of the plant. Objective: The objective of this parallel arm, double-blind randomised controlled phase III trial is to establish the efficacy and safety of Gymnema lactiferum. Methods: Eligible type 2 diabetes mellitus (T2DM) patients at the Diabetic Centre, Teaching Hospital Jaffna, Sri Lanka were randomly allocated to treatment (n = 160) and control (n = 160) arms. The treatment arm received a tea brew made of G. lactiferum dried leaves (1.5 g in 200 mL of hot water) while the control arm received green tea (1.5 g in 200 mL of hot water) daily for 3 months. The patients in both arms were reviewed at the baseline and the end of 1st, 3rd and 6th months for FPG, HbA1c, blood pressure, body weight and lipid profiles. Results: Statistically significant reductions in HbA1c (treatment arm: -0.47 %, P = 0.0000; control arm -0.26 %, P = 0.0009) and FPG (the control arm: −0.42 mmol/L, P = 0.0388) from the base values were observed at the end of the 3rd month. In the subgroup analysis that evaluated the participants with poorly controlled glycemia (HbA1c ≥8), which accounted for over 52 % of all participants, a clinically significant reduction in HbA1c was observed in the treatment and control arms (-0.90 %; P = 0.0000 and -0.71 %; P = 0.0000). Post-intervention analysis revealed a long-lasting significant reduction in HbA1c in both arms. Further, significant reductions in blood pressure and lipid profile were also noted at the end of the third month and post-intervention period. Conclusion: G. lactiferum tea significantly reduced HbA1c in uncontrolled T2DM patients and the effect observed was superior to green tea. Long-term treatment is needed to determine the clinical implications of the effects on blood pressure, body weight and lipid levels and to confirm the safety
Keywords: Type 2 diabetes(T2DM); Diabetes mellitus; Metabolic diseases; Dyslipidaemia; Gymnema; Gymnema lactiferum; Complementary medicine